IMPLEMENTATION OF PROJECT-BASED LEARNING IN TEACHING WRITING: KEY CONCEPTS AND STAGES - Irpan Apandi Batubara; Bachrudin Musthafa; Wawan Gunawan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTProject-Based Learning (PjBL) has gained popularity as an approach to language teaching over the recent decade. However, previous studies have highlighted that PjBL is often applied in diverse contexts. This study aims to identify the key concepts and stages of PjBL implementation in teaching writing within the context of higher education in Indonesia. The research approach was a case study that utilized observation and interviews. The participant was a lecturer who actively incorporated PjBL into their teaching. The data were analyzed using content analysis. The findings reveal several stages of PjBL in teaching writing, including posing essential questions, planning and scheduling, outlining, developing the outline into a draft, monitoring progress, presenting the first draft, reviewing and editing, finishing, and publishing, and evaluating and reflecting. Furthermore, the study identifies key concepts of PjBL in teaching writing, such as driving questions, process and product orientation, student ownership, extended project duration, natural integration of skills, dual commitment to language and learning, group work obligation, student responsibility for information gathering, processing, and reporting, assumed new roles and responsibilities for students and teachers, collaboration, and reflection. This study also sheds light on how PjBL can be applicable in teaching writing.ABSTRAKPembelajaran Berbasis Proyek (PjBL) telah menjadi metode pengajaran bahasa yang populer dalam dekade terakhir. Studi sebelumnya menunjukkan bahwa PjBL sering diterapkan dalam berbagai konteks. Penelitian ini bertujuan mengidentifikasi konsep dan tahapan PjBL dalam mengajar menulis di perguruan tinggi di Indonesia. Penelitian ini menggunakan pendekatan studi kasus dengan observasi dan wawancara pada seorang dosen yang aktif menerapkan PjBL. Analisis konten digunakan untuk menganalisis data. Temuan penelitian menunjukkan beberapa tahapan PjBL dalam mengajar menulis, seperti merumuskan pertanyaan esensial, perencanaan, pembuatan kerangka, pengembangan draf, pemantauan kemajuan, presentasi draf pertama, peninjauan dan pengeditan, penyelesaian dan publikasi, serta evaluasi dan refleksi. Studi ini juga mengidentifikasi konsep-konsep kunci PjBL, seperti pertanyaan pokok, orientasi pada proses dan produk, kepemilikan siswa, durasi proyek yang diperpanjang, integrasi alami keterampilan, komitmen ganda terhadap bahasa dan pembelajaran, kewajiban kerja kelompok, tanggung jawab siswa dalam pengumpulan, pengolahan, dan pelaporan informasi, peran baru siswa dan guru, kolaborasi, dan refleksi. Penelitian ini memberikan wawasan tentang penerapan PjBL dalam mengajar menulis.How to Cite: Batubara, I. A., Musthafa, B., & Gunawan , W. (2023). Implementation of Project-Based Learning in Teaching Writing: Key Concepts and Stages. IJEE (Indonesian Journal of English Education), 10(2), 301-322. doi:10.15408/ijee.v10i2.32452.